LANGUAGE ATTITUDES AND MOTIVATION FOR LEARNING INDONESIAN LANGUAGE AS A FOREIGN LANGUAGE BY STUDENTS OF MALAY-INDONESIA DEPARTMENT, HANKUK UNIVERSITY OF FOREIGN STUDIES (HUFS) SOUTH KOREA - Lukman, Lukman (JURNAL ILMU BUDAYA, 2019)
There are two major factors which influence a person to learn and master a foreign language. These are language attitude and motivation. The aim of this study is to understand how language attitude and motivation of students in Hankuk University of Foreign Studies (HUFS) South Korea affect learning the Indonesian Language. Questionnaires were distributed to 20 students of Malay-Indonesian Department at HUFS, South Korea. The data obtained from the questionnaires were then analyzed by using a scale for measuring attitude (Likert scale). Based on the Likert scale analysis, the results indicated that their language attitudes had an average value of 3.87 (the scale ranges from 1 to 5). This implies that they have a  positive attitude. In a similar manner, the analysis of their motivations shows that their average score is 4.22. Their motivation to learn the Indonesian Language is very positive, that is, very high. This high score is in the aspect of an instrumental motivation with an average score of 4.35. The results of this study show that a positive language attitude and motivation enables the learners to achieve success in learning a foreign language.